Batch cocktails : make-ahead pitcher drinks for every occasion - Hoffman, Maggie (Food and drink writer) (Ten Speed Press, 2019)
As anyone who has hosted a dinner party knows, cocktail hour is the most fun part of the evening for guests--but the most stressful for whomever is in charge of keeping the drinks flowing. The solution, though, is simple: batch it! In this fun collection, Maggie Hoffman offers 65 delicious and creative cocktails that you don't have to stir or shake to order; rather, they are designed to stay fresh when made ahead and served out of a pitcher. Recipes such as Tongue in Cheek (gin, Meyer lemon, thyme, Cocchi Rosa), Friendly Fires (mezcal, chile vodka, watermelon, lime), Birds & Bees Punch (rum, cucumber, green tea, lemon), and even alcohol-free options are organized by flavor profile--herbal, boozy, bitter, fruity and tart, and so on--to make choosing and whipping up a perfect pitcher of cocktails a total breeze.